Dual Identity, Minority Group Pressure, and the Endorsement of Minority Rights: A Study among Sunni and Alevi Muslim in Western Europe. (8th May 2019) - Cárdenas, Diana
Abstract: Research has found that migrants with strong dual identities (e.g., Muslim German) are more likely to endorse the rights of their minority group. This article aims to contribute to the literature by examining whether dual identity predicts stronger endorsement of minority rights when migrants perceive pressure to conform from their minority community. This is examined in two subgroups that tend to exert different pressures: Alevi and Sunni Muslims. Muslim migrants ( n Sunni = 464; n Alevi = 235) in Germany and the Netherlands answered questions about dual identity, endorsement of Muslim rights, and perceived minority pressure. For Alevi Muslims, dual identity predicted greater minority rights as minority pressure increased. For Sunni Muslims, the opposite pattern was found, with dual identity predicting less minority rights as minority pressure increased. These findings highlight the importance of studying different minority communities, and their pressures, to understand the societal ramifications of dual identities.